Penerapan Metode Design Thinking dan Agile Development Pembangunan Aplikasi Marketplace “Hijab” - Anis Lelitasari; Reza Ilyasa; Rangga Gading Satria; Nurdin Effendi; Muhammad Qaddasa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of information technology is growing increasingly rapidly, many activities have been helped by technology, one of which is the process of buying and selling transactions. At this time people prefer to make buying and selling transactions online, this is because it can facilitate transactions such as seeing the details of the goods, the transaction process is easier and more efficient. Currently, hijab producers in the cikarang area who have a large market in work channeling institutions (LPK) to Japan market merchandise to interns directly or manually not utilizing technology. The current manual transaction process has many disadvantages including the need for a place, time for the buying and selling process, the process of recording transactions often makes mistakes. Things like this cause problems both from the seller or buyer side. From the problems that occur, a mobile marketplace application system